(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the impact of disrupted resources on the local economy through a case study of Mahroqa Cement Factory. An applied analytical field approach was employed, collecting data through questionnaires and interviews with factory management and employees, alongside analyzing production and price data. The findings indicate that disruptions in key resources, such as electricity, fuel, and raw materials, significantly reduce productivity, lead to job losses, increase local unemployment, and raise cement and related material prices. Furthermore, weak management and government policies exacerbate these effects, whereas economic interventions and administrative reforms help mitigate them. Statistical analyses confirmed significant relationships among the five study variables, with large effects on production, employment, and prices. The study recommends ensuring stable resource supply, improving administrative policies, enhancing worker skills, and establishing strategic reserves of energy and raw materials to support industrial sustainability and minimize the adverse impacts of resource disruptions.